2023
DOI: 10.3390/diagnostics13111841
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Optical Genome Mapping in Cytogenetic Diagnostics of Hematological Neoplasms: A New Way to Look at DNA

Abstract: Optical genome mapping (OGM) is a new genome-wide technology that can reveal both structural genomic variations (SVs) and copy number variations (CNVs) in a single assay. OGM was initially employed to perform genome assembly and genome research, but it is now more widely used to study chromosome aberrations in genetic disorders and in human cancer. One of the most useful OGM applications is in hematological malignancies, where chromosomal rearrangements are frequent and conventional cytogenetic analysis alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…OGM is a new genomic technology that can reveal SVs, CNVs, and whole-chromosome aneuploidies in a single experiment [ 13 ]. OGM electrophoreses ultra-long high-molecular-weight DNA (> 150 kb) into nanochannels, linearizing them for imaging, and creates a consensus genome map from the processed images [ 13 ].…”
Section: Advances In Genomic Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…OGM is a new genomic technology that can reveal SVs, CNVs, and whole-chromosome aneuploidies in a single experiment [ 13 ]. OGM electrophoreses ultra-long high-molecular-weight DNA (> 150 kb) into nanochannels, linearizing them for imaging, and creates a consensus genome map from the processed images [ 13 ].…”
Section: Advances In Genomic Technologiesmentioning
confidence: 99%
“…OGM is a new genomic technology that can reveal SVs, CNVs, and whole-chromosome aneuploidies in a single experiment [ 13 ]. OGM electrophoreses ultra-long high-molecular-weight DNA (> 150 kb) into nanochannels, linearizing them for imaging, and creates a consensus genome map from the processed images [ 13 ]. Recent studies have highlighted the advantages of OGM as an emerging genomic technology for hematologic malignancies, which can potentially replace conventional cytogenetic diagnostics [ 13 15 , 55 60 ].…”
Section: Advances In Genomic Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also known as "Next Generation Cytogenetics", this method exploits DNA labeling rather than sequencing and is considered a link between techniques based on sequencing and whole chromosome analysis [11][12][13]. Several studies have tested this technology to identify genomic aberrations in both constitutional syndromes and tumors [12,14], demonstrating that OGM is particularly effective in defining complex genomic rearrangements [13,15] such as chromothripsis, consisting of hundreds of genomic rearrangements caused by the shattering of a chromosome and the random reassembly of the generated genomic fragments [16][17][18]. Considering these peculiarities, OGM is frequently applied to the study of hematological diseases, where complex karyotypes are frequent and conventional cytogenetic analysis alone is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A growing number of studies have recently demonstrated the efficiency and superiority of OGM in various clinical settings, including both prenatal and postnatal congenital conditions, as well as various hematological and other malignancies. [5][6][7] Here, we explore the value of OGM in identifying cryptic BCRs using a case series from our clinical practice. This study was approved by the ethics committee of the Nanjing Drum Tower Hospital affiliated with Nanjing University Medical School (no.…”
mentioning
confidence: 99%